Parents' Perception Of Image Towards School Choice Decision Making: PLS-SEM Analysis - Eka Mulyani; Yetri Yetri; Aditia Fradito; Riyuzen Praja Tuala (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Increasing competition among educational institutions requires schools to continuously improve the quality of their services and build a positive image of their institutions within the community. School image is an important factor influencing parents' perceptions in assessing the quality, reputation, and credibility of educational institutions, particularly in determining school choice for their children. This study aims to analyze the influence of parents' perceptions of school image in the decision-making process of choosing a school at SMP Islam Az Zahra Bandar Lampung. The method used is quantitative with an explanatory design through the distribution of questionnaires to parents as research respondents. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The results of the analysis show that parents' perceptions of school image have a significant influence on the decision-making process of choosing a school with a t-statistic value of 19.780 and a p-value of 0.000. In addition, the R-square value of 0.762 indicates that parents' perceptions of school image can explain 76.2% of the variation in parents' decisions in choosing a school. These findings confirm that a school's image, reflecting academic quality, institutional reputation, and the integration of Islamic values, plays a crucial role in shaping parental trust and preference for Islamic educational institutions. Therefore, schools are advised to continue strengthening their institutional image management by improving the quality of educational services and effective communication with parents.